Meeting the needs of the whole child through effective early childhood care, education and evaluation (2016)
The education of children during the earliest years of their life lays the foundation for all other developmental processes that follow. The nature and quality of care, the experiences and the learning opportunities offered to children from birth through infancy and early childhood, tend to affect their educational potential and their life chances in a lasting way. The globally recognised and the Nigerian government, of the importance of early years have resulted in a sharp interest and increase in the provision of early childhood care and education. Furthermore, in Nigeria, considerable energy and efforts have been directed into encouraging uniformity and advocating the improvement in the many and diverse services which at present cater for Nigerian children before they reach full-time mainstream primary education. The reasons for these provisions may not be far from the theme of this conference - to meet the needs of *"Nigerian child at the very beginning. Thus, the process through which practitioners as well as researchers could follow to ensure that, effective inculcation and exhibition of the expected behavioural outcomes need to be looked into. Understanding who the child is and the behaviours expected from the child to exhibit at every stage of development could help in effective early childhood provision. Thus, the proposed use of developmentally appropriate indicators could help in benchmarking acceptable practices at the pre-school level. Benchmarking helps in linking the internal processes to external expectations, which can be compared with best practices anywhere in the world.